Inappropriate use of prescribed psychotropic drugs: Intravenous diazepam in the psychiatric emergency. - Quispe-Turpo, Fabiola (2021)
Benzodiazepines (BZDs) are essential drugs used in the treatment of different health problems: Peru’s National Drug Petitionary lists five of them allowed for oral or parenteral administration. At the beginning in the 1960s, BZDs were widely and unrestrictedly prescribed; the subsequent development of tolerance and withdrawal phenomena, triggered by their prolonged use, led to drastic prescription restrictions,  sometimes below the real clinical needs. Although BZDs are included in the Drug Enforcement Administration (DEA) group IV of controlled substances, it is accepted that, in general, they are not primary drugs of abuse, and the development of addictive phenomena only occurs in the presence of comorbidity with other drug addictions. It is necessary to distinguish between the "inappropriate use" or "misuse" of the BZDs and those cases that meet criteria of full dependence. There are few reported cases of inappropriate use of BZD prescribed  by parenteral route. The case reported here is one of a 51-years-old woman who, over the course of several years, went to a psychiatric emergency service due to crisis of dysphoria and anxiety (but not a panic attack), and received on several occasions, intravenous injections of diazepam, to the point that later she used to go repeatedly to demand such medication, without being medically necessary. It is, therefore, important for the prescribing professional to use parenteral BZDs cautiously and carefully, in order to prevent an addictive process that can generate serious consequences.